(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the comparative-typological character, analytic learning of creative person, as well as, history and classification of creative person’s character. It is analyzed that creative person’s character by comparative- typological way on A. Kahhor’s novel “Sarob”(Mirage) and Jack London‘s “Martin Eden”